2021
DOI: 10.4168/aair.2021.13.4.560
|View full text |Cite|
|
Sign up to set email alerts
|

Lacticaseibacillus casei AMBR2 Restores Airway Epithelial Integrity in Chronic Rhinosinusitis With Nasal Polyps

Abstract: Purpose A defective epithelial barrier has been demonstrated in chronic rhinosinusitis with nasal polyps (CRSwNP). Lactobacilli are shown to restore epithelial barrier defects in gastrointestinal disorders, but their effect on the airway epithelial barrier is unknown. In this study, hence, we evaluated whether the nasopharyngeal isolates Lacticaseibacillus casei AMBR2 and Latilactobacillus sakei AMBR8 could restore nasal epithelial barrier inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…To the best of our knowledge, documentation on such barrier-enhancing effects on the URT epithelium is scarce. Recently, we have also found barrier-protective effects for the URT isolate L. casei AMBR2 ( Martens et al., 2021 ). Notably, compared to D. pigrum , L. casei has a weaker association with the nose as its main habitat based on its lower prevalence and relative abundance in the URT ( De Boeck et al., 2020 ) and its association with more habitats as nomadic species ( Duar et al., 2017 ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…To the best of our knowledge, documentation on such barrier-enhancing effects on the URT epithelium is scarce. Recently, we have also found barrier-protective effects for the URT isolate L. casei AMBR2 ( Martens et al., 2021 ). Notably, compared to D. pigrum , L. casei has a weaker association with the nose as its main habitat based on its lower prevalence and relative abundance in the URT ( De Boeck et al., 2020 ) and its association with more habitats as nomadic species ( Duar et al., 2017 ).…”
Section: Discussionmentioning
confidence: 82%
“…Both immune signaling and pathogen killing likely play a role in the beneficial action of D. pigrum ; however, understanding the detailed role of each of these mechanisms would require detailed dedicated research at the molecular level. TLR activation by D. pigrum was also explored in the present study, as these receptors are involved in epithelial barrier functioning, with TLR2/6 activation generally linked to barrier-enhancing and anti-inflammatory signaling effects; however, TLR2/1 is rather involved in inflammation and barrier-disruptive effects ( Martens et al, 2021 , 2021 ; Yuki et al., 2011 ). We observed that D. pigrum strongly activated the TLR2/TLR6 heterodimer, even stronger than L. casei AMBR2 ( Martens et al., 2021 ) and S. aureus, the latter mainly inducing TLR1/6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an alternative formulation such as a nose spray instead of the used throat spray, might be more favorable, since SARS-CoV-2 receptors are highly expressed in nasal epithelium, and the alpha variant that was dominant during the study has been shown to primarily target the nose [27]. In addition, based on in-house previous research, the selected lactobacilli have several beneficial modes of action such as antimicrobial and immunomodulatory properties, as well as barrier enhancing effects in the nasal epithelium [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue, Martens et al . 7 aimed to investigate the effect of Lacticaseibacillus casei AMBR2 ( L. casei AMBR2) on nasal epithelial barrier function of human primary nasal epithelial cells (pNECs) in CRSwNP patients. They also reported that the anterior nares and nasopharynx of CRSsNP and CRSwNP patients had significantly low relative abundance of lactobacilli compared to controls.…”
mentioning
confidence: 99%